High-density lipoprotein (HDL) functionality and its relevance to atherosclerotic cardiovascular disease - Constantine E Kosmas; Ian Martinez; Andreas Sourlas; Kyriaki V Bouza; Frederick N Campos; Verenisse Torres; Peter D Montan; Eliscer Guzman (BioExcel Publishing Ltd, 2018)
Several prospective epidemiological studies have shown that there is a clear inverse relationship between serum highdensity lipoprotein-cholesterol (HDL-C) concentrations and risk for coronary heart disease (CHD), even at low-density lipoprotein-cholesterol (LDL-C) levels below 70 mg/dL. However, more recent evidence from genetic studies and clinical research has come to challenge the long-standing notion that higher HDL-C levels are always beneficial, while lower HDL-C levels are always detrimental. Thus, it becomes apparent that HDL functionality plays a much more important role in atheroprotection than circulating HDL-C levels. HDL cholesterol efflux capacity (CEC) from macrophages is a key metric of HDL functionality and exhibits a strong inverse association with both carotid intima-media thickness and the likelihood of angiographic coronary artery disease (CAD), independent of the HDL-C level. Thus, extensive research is being conducted to identify new agents with a favorable side effect profile, which would be able to enhance CEC, improve HDL functionality and potentially decrease cardiovascular risk. This review aims to present and discuss the current clinical and scientific evidence pertaining to the significance of HDL functionality over the actual HDL-C concentration in mediating the favorable effects on the cardiovascular system. Thus, we conducted a PubMed search until December 2017 through the English literature using the search terms 'HDL function/ functionality', 'HDL properties', 'cardiovascular risk' and 'cholesterol efflux capacity'. We also included references from the articles identified and publications available in the authors' libraries.